True Nature of Supply Network Communication Structure - Hakim bin Osman, Lokhman (International Research Journal of Business Studies, 2016)
Globalization of world economy has altered the definition of organizational structure. Global supply chain can no longer beviewed as an arm-length structure. It has become more complex. The complexity demands deeper research and understanding. This research analyzed a structure of supply network in an attempt to elucidate the true structure of the supply network. Using the quantitative Social Network Analysis methodology, findings of this study indicated that, the structure of the supply network differs depending on the types of network relations. An important implication of these findings would be a more focus resource management upon network relationship development that is based on firms’ positions in the different network structure. This research also contributes to the various strategies of effective and efficient supply chain management.